2016
DOI: 10.4038/sljch.v45i1.8083
|View full text |Cite
|
Sign up to set email alerts
|

A study on cholestasis in infants less than six months of age presenting to Lady Ridgeway Hospital for Children, Colombo

Abstract: Objectives: To determine the common clinical presentations, common aetiological factors, average age at presentation and possible means of early detection of cholestasis by primary health care workers. Method: This prospective, descriptive study analyzed 60 infants less than six months old who presented to Lady Ridgeway Hospital from October 2013 to January 2015 with evidence of cholestasis. Results: The common clinical features were jaundice (100%), hepatomegaly (83.3%), pale stools (76.6%), dark urine (61.6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Regarding other findings, this study revealed the same patients by examination and by Abd U/S presented with hepatomegaly (77.1%), which is nearly similar to results of (76.4%) reported by Iranian study [18] (51.7%) respectively with hepatomegaly. Totally (54.3%) of patients presented with splenomegaly depending on U/S finding, which closes to results by MIM Luthufdeen et al [16] (2016) with (56.6%) while the result of N. Urganci et al [10] (2011) and of Dehghani SM.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding other findings, this study revealed the same patients by examination and by Abd U/S presented with hepatomegaly (77.1%), which is nearly similar to results of (76.4%) reported by Iranian study [18] (51.7%) respectively with hepatomegaly. Totally (54.3%) of patients presented with splenomegaly depending on U/S finding, which closes to results by MIM Luthufdeen et al [16] (2016) with (56.6%) while the result of N. Urganci et al [10] (2011) and of Dehghani SM.…”
Section: Discussionsupporting
confidence: 87%
“…The oral Valganciclovir is a promising drug for CMV infection [10,36,37]. In 84.6% cases of CMV (with Valganciclovir) and 50% cases of CMV with HSV (with Valganciclovir and Acyclovir) improved.…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic neonatal hepatitis (INH) and biliary atresia (BA) are the most commonly observed causes of cholestatic jaundice in the first months of life [8,9]. Idiopathic, congenital infection, sepsis, and inborn errors of metabolism are relatively more common causes of neonatal hepatitis compared to toxic causes, post-hemolytic states, neonatal acute hepatic necrosis, parenteral nutrition, and chromosomal anomalies as well as familial syndromes [10]. Among Asians, alpha-1 antitrypsin (α1AT) deficiency is uncommon but common among Caucasians [11].…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of neonatal cholestasis or biliary atresia in Sri Lanka (SL) or South Asia is not known. However, it is estimated that biliary atresia accounts for 26-36% of neonatal cholestasis in this region [4].…”
Section: Introductionmentioning
confidence: 99%